2010
DOI: 10.3802/jgo.2010.21.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of tumor volume and lymph node involvement assessed by MRI in stage IIB cervical cancer patients treated with concurrent chemoradiation therapy

Abstract: Objective: The purpose of this study was to evaluate the prognostic significance of tumor volume assessed by pretreatment MRI in stage IIB cervical cancer patients with concurrent chemoradiation therapy. Methods: A retrospective chart review was performed on seventy five patients with cervical cancer who were treated with concurrent weekly cisplatin (40 mg/m 2 ) and radiotherapy between January 2000 and April 2007. Potential prognostic factors were age, chemotherapy numbers, histology, tumor diameter and volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…Tumor size more than 8 cm in diameter or more than 35 cc volumes showed worse survival outcomes (Lee et al, 2010). Tumor size also predicted the risk of lymph node metastasis and ultimately the survival outcomes.…”
Section: Benefits For Determination Of Prognosismentioning
confidence: 95%
“…Tumor size more than 8 cm in diameter or more than 35 cc volumes showed worse survival outcomes (Lee et al, 2010). Tumor size also predicted the risk of lymph node metastasis and ultimately the survival outcomes.…”
Section: Benefits For Determination Of Prognosismentioning
confidence: 95%
“…10 Imaging techniques such as magnetic resonance imaging (MRI), computed tomography (CT), 18-°urodeoxyglucose-positron emission tomography ([ 18 F] FDG-PET) and singlephoton emission computed tomography (SPECT), which provides an indication of the metabolic and proliferative activity within tumors, have also been pursued for prediction of tumor response. Though these techniques have shown to be potential, wide variation in data collection and analysis are some of the known limitations.…”
Section: à9mentioning
confidence: 99%
“…Among the metabolic parameters of the primary tumor and the lymph nodes, the nodal SUVmax was the most powerful prognostic marker for the prediction of recurrence. Stage, tumor size, and lymph node status have been recognized as important predictors of the prognosis with respect to patient survival [2,3]. In addition, it has been well demonstrated that the survival rate of patients with cervical cancer with lymph node metastasis is significantly lower than that of patients without lymph node metastasis [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Advanced International Federation of Gynecology and Obstetrics (FIGO) stage, larger tumor size, and presence of lymph node metastasis have been reported as negative prognostic factors for patients with cervical cancer who are treated with concurrent chemoradiotherapy (CCRT) [2,3]. Pelvic and/or paraaortic lymph node status is a strong independent prognostic factor in cervical cancer [4,5].…”
Section: Introductionmentioning
confidence: 99%